Recognition and eradication of prime artefact from the abdominal electrocardiogram. (2016) - Anisha, M.; Kumar, S.S.; Benisha, M.
This paper proffers an algorithm that recognises and eradicates Maternal Electrocardiogram (MECG), the supreme dominant artefact from the multichannel abdominal Electrocardiogram to diagnose the presence of foetal heart deformities. The proffered technique has three stages; initial pre-processing stage computes averaged Abdominal Electrocardiogram (AECG) from multichannel AECG realisations. At the second stage Smoothed Pseudo Wigner-Ville Distribution (SPWVD) time-frequency analysis has been performed for energy calculation which is intrinsic in the identification of maternal R peaks, fiducial points and maternal P, T waves. Last stage eradicates the entire maternal influence by subtracting the mean of subsequent identified maternal PQRST repetitions. This work is validated using multichannel abdominal Electrocardiogram acquired from the physionet non-invasive foetal ECG databank.